(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The Agave weevil (Scyphophorus acupunctatus Gyll.) adults was collected in Sicily during 2006-07 on Agave americana and rearing in insectary. The adult beetles are about 18 mm long and black. The males have the first abdominal sternum strongly evenly concave and have a difference in the shape and convexity of the pygidium and that should be checked by the people doing the sexing. The adults create tunnels through the leaves as they eat, and the females lay eggs within these holes. The grubs have no legs and move about with a rippling motion of their body. Once the grubs hatch, they feed on the new leaves at the center of the plant, which then usually becomes infected by bacteria Erwinia carotovora. This is the source of the rancid smelling brown slime. The grubs seem to feed right in the brown mess and later pupate using plant fibers to create a cocoon. In the laboratory at room temperature, a generation took place from April to August in approximately 120 days. The monitoring carried out during 2007 in some town of eastern Sicily has not so far led to the identification of other outbreaks of infestation.